Application of non-commercial ceramic cutting tool in machining of hardened stainless steel - De Paula, M A [UNESP]; De Sousa, T A [UNESP]; Csouza, J. V. [UNESP]; Alves, M. C.S. [UNESP]; Ribeiro, M. V. [UNESP] (IOP Publishing, 2019)
The current competition in the industry requires the development of more resistant materials for applications in engineering projects. Hardened AISI 410 martensitic stainless steel is one of these materials. In machining these materials there is a greater wear of cutting tools. Therefore, the research and development of new cutting tools that meet the specific requirements of the machining process of these materials are important. In the development of new cutting tools, it is possible to use the Design of experiments as a tool to optimize the machining process. The objective of this work was to evaluate the machining process by turning of the hardened AISI 410 martensitic stainless steel in the dry machining condition using a non-commercial ceramic tool (Al2O3?+?MgO). The machining tests were performed on aROMICNCmodel GL 240 M, maximum rotation of 4500 rpm and 18 kWof maximum power. The following cutting parameters used in the machining: Cutting speed (400-500-600mmin-1), feed rate (0.05-0.1-0.2-0.3mmrev-1) and depth of cut (0.5mm). The parameters of the experiment analyzed were flank wear (VBmax), roughness (Ra) and (Rt) and vibration. In the analysis of cutting tool wear, it was used optical microscopy with scanning electron microscope (SEM). In general, the best results for the response variables obtained with cutting speed (400mmin-1) and feed rate (0.05 and 0.1mmrev-1). This combination showed the lowest values of flank wear, roughness and vibration (in this case, smaller is better). There was a tendency for better results in the response variables for lower cutting speed values combined with lower feed rates. The abrasion mechanism was present in several experiments and its presence is very evident in the cutting tools for cutting speed values of 400mmin-1 and feed rate of 0.05 and 0.1mmrev-1.
Keywords: Aisi 410; Ceramic cutting tool; Doe; Dry machining; Turning; Wear